PERBEDAAN PERSEPSI MEROKOK ANTARA SISWA - Dewi Ratna Puspitasari; Muhammad Hasib Ardani Hasib Ardani (Jurnal Keperawatan Diponegoro, 2012)
A child generally likes to pay attention and do something by his parents. One of unhealthy behaviors of parents is smoking. Parents who smoke will affect the child's perception of smoking. The purpose of this study was to determine whether the perceptions of smoking among male students at primary school (IV – VI grade) differ with parents who smoke and not smoke in the Gugus Ki Hajar Dewantoro Rembang. This study was a quantitative with a survey approach recruited 176 respondents of elementary male students (IV-VI grade) in the Gugus Ki Hajar Dewantoro Rembang. The instrument in the study was a questionnaire for male students perception of smoking in elementary. The process and analysis data used statistical method. The results showed any differences male students perceptions of smoke among elementary school (IV - VI grade) with fathers who smoke and not smoke where ρ-value was 0,000 at α 0.05. The conclution there were perceptions differences of smoking among male students at primary school (IV – VI grade) with parents who smoke and not smoke.Therefore, parents must provide a correct knowledge and a good example of smoking so that students have a negative perception or disagree with smoking